Technology in older hands: A pilot study on digital literacy and attitudinal changes in old age Technology in older hands - Ureta Fernández, María del Pilar; Agüero Jiménez, Amaru; Cerda Díez, María Fernanda (Revista Española de Comunicación en Salud, 2026)
Introduction: The rapid digital transformation of contemporary societies poses new challenges for older adults, who generally present lower levels of digital literacy compared to other age groups. Objective: This pilot study aimed to evaluate the impact of a structured digital literacy intervention on attitudes toward and use of smartphones among older adults in Chile. Methodology: A quasi-experimental pretest–posttest design was applied to 71 participants (≥60 years) who completed a four-session program focused on smartphone use for communication, information searching, and online procedures. Results: Quantitative analysis showed significant improvements across all evaluated dimensions: perceived usefulness, comfort, control, and frequency of use (Wilcoxon test, p
Keywords: digital literacy; aged; smartphone; digital divide; educational intervention